Harmonic AC magnetic susceptibility analysis of FeSe crystals with composite morphology. (23rd May 2019) - Buchkov, K; Galluzzi, A; Mancusi, D; Nazarova, E; Pace, S; Polichetti, M
Abstract: The AC magnetic response of multi-domain FeSe crystals has been explored by means of fundamental and third harmonic AC magnetic susceptibility (ACMS) analysis. Our previous studies have revealed a complex morphology which especially modifies the mixed state properties. The effects were expressed by an additional 'pseudo' peak feature of the magnetic hysteresis and in the present study we analyze its vortex dynamics nature and irreversibility behavior in the context of ACMS. We find that the effect is detectable mainly with the sensitive third harmonic component and especially at high AC field frequencies. From the analysis, the temperature dependence of the 'pseudo' peak effect at different DC fields ranges was determined, confirming the previously established superconductor–normal metal–superconductor type links between the domains in the crystal. The irreversibility line, the most important parameter for high power applications, shows a typical glass/liquid transition in the vortex matter. In addition we have observed surface barrier effects and vortex avalanche activity, the behavior of which appears to be influenced by the superconducting and magnetic nature coexistence and morphology. The presented results show the effective application of the harmonic AC magnetic susceptibility technique for a versatile analysis of complex nonlinear phenomena in materials with a sophisticated AC magnetic response.